PERAN SENTRAL KEARIFAN LOKAL DALAM PENINGKATAN KUALITAS PENDIDIKAN - Rendra Sakbana Kusuma (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
Education can improve the degree of human life. The decline in the competitiveness of Indonesian workers is an evaluation of the role and function of education in Indonesia. Indonesia is the most populous country in Southeast Asia and most of its population works overseas as unskilled laborers. The role and function of education is being questioned, considering that education is the most appropriate tool to obtain a better future. Indonesia with its characteristic as an archipelago and has many ethnic groups and cultures is very different from other countries. Indonesia has thousands of islands, thousands of tribes, ethnicities, and cultures that should be used as the strength in supporting the creation of higher quality education. Indonesia through the local wisdom possessed by each region is expected to be able to become an excellence in creating globally oriented education and based on local wisdom. The values of local wisdom can be included in various joints in the implementation of education held based on the principles of the implementation of education.